2019
DOI: 10.1002/lno.11145
|View full text |Cite
|
Sign up to set email alerts
|

Fear and food: Effects of predator‐derived chemical cues and stoichiometric food quality onDaphnia

Abstract: While resource quality and predator-derived chemical cues can each have profound effects on zooplankton populations and their function in ecosystems, the strength and direction of their interactive effects remain unclear. We conducted laboratory experiments to evaluate how stoichiometric food quality (i.e., algal carbon [C] : phosphorus [P] ratios) affects responses of the zooplankter, Daphnia pulicaria, to predator-derived chemical cues. We compared growth rates, body P content, metabolic rates, life-history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The significant reduction in the body size of neonates may be due to the following two reasons. On the one hand, energy allocation is insufficient, as fish kairomone require the mother C. cornuta to allocate more energy to produce offspring earlier and to increase the number of offspring produced (Reede 1995;Mikulski 2001;Bell et al 2019); on the other hand, calcium allocation is inadequate, which has a maternal effect (Giardini et al 2015), that is, the maternal calcium is not enough to distribute to more neonates. A previous study demonstrated that the body size of cladocerans at maturation has a minimum threshold, and only when cladocerans reach the threshold of body size can they develop to maturity and start the stage of reproduction (Ebert 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant reduction in the body size of neonates may be due to the following two reasons. On the one hand, energy allocation is insufficient, as fish kairomone require the mother C. cornuta to allocate more energy to produce offspring earlier and to increase the number of offspring produced (Reede 1995;Mikulski 2001;Bell et al 2019); on the other hand, calcium allocation is inadequate, which has a maternal effect (Giardini et al 2015), that is, the maternal calcium is not enough to distribute to more neonates. A previous study demonstrated that the body size of cladocerans at maturation has a minimum threshold, and only when cladocerans reach the threshold of body size can they develop to maturity and start the stage of reproduction (Ebert 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of inducible predator‐resistant traits involves a series of complex processes, including the identification of chemical signals and resource allocation (Effertz and von Elert 2014;Bell et al 2019; Gu et al 2020); thus, the type and intensity of expression of these traits and their subsequent effects on the population dynamics of prey can be affected by environmental conditions. Many studies have found that the ability of some aquatic organisms to form induced defense varies with temperature (Zhu et al 2019), food types (Bell et al 2019; Gu et al 2020), availability of nutrients (Zhu et al 2016), CO 2 concentration (Huang et al 2018), UVB radiation stress (Rose et al 2012; Sun et al 2020), light intensity (Effertz and von Elert 2014), pollutants (Pestana et al 2010; Huang et al 2016; Zhu et al 2020), and salinity (Bezirci et al 2012). It is well known that calcium is an important element in signal transduction (Clapham 2007) and can change the material and energy distribution of organisms (Pérez‐Fuentetaja and Goodberry 2016; Huang et al 2020).…”
mentioning
confidence: 99%
“…They are represented by direct metabolic demands, e.g., due to increased respiration rate [23,203], or direct energy and material costs for forming and maintaining defences, such as morphological structures or increased reproduction (e.g., [99,[194][195][196]). Several studies already reported increasing demands of nutrients with increasing predation risk, or reduced defence expression under nutritional constraints [99,[204][205][206][207][208]. However, it is difficult to estimate allocation costs with definite numbers, as it is not easy to determine whether the resources are allocated into a defence, like PUFAs that are needed for increased reproduction [75], or whether constraints are caused by other factors as well, such as the previously mentioned increase in PUFA demand due to low temperatures.…”
Section: Costs For Inducible Defencementioning
confidence: 99%
“…12–33°C. We provided food at a fixed quantity of 4 mg C/L at the start of the experiment and on days 2 and 4, which correspond to rations in similar previous experiments found to support fast Daphnia growth (Bell et al., 2019; Prater et al., 2016; Wagner & Frost, 2012). Temperature was controlled by holding animals in temperature‐controlled growth chambers.…”
Section: Methodsmentioning
confidence: 99%